The Impact of Service Quality, Product Quality, and Innovation on Customer Satisfaction through Advocacy Model for SMEs Baby Shops in Jabodetabek: The Impact of Service Quality, Product Quality, and Innovation on Customer Satisfaction through Advocacy Model for SMEs Baby Shops in Jabodetabek - Mulyadi, Maria Novena (Sekolah Tinggi Manajemen IPMI, 2024)
The infant and maternity market in Indonesia is expected to expand in the coming years as a result of rising purchasing power. This study aims to examine the effect of service quality, product quality, and innovation on customer satisfaction, as well as the influence of advocacy on SMEs baby shop customers in Indonesia. Purposive sampling was utilized to collect a total sample of 112 responses from Jabodetabek customers. The data used to test the hypotheses were obtained through a questionnaire and processed quantitatively using SPSS and SEM PLS. The study find that there are positive effect on service quality, product quality and innovation to customer satisfaction. Also there is positive effect on product quality, innovation, customer satisfaction to advocacy. Just one hypothesis that rejected, that is no effect for service quality to advocacy. This study focus on examine which variable impacted the most to customer satisfaction and advocacy trait toward SMEs baby shop business in Jabodetabek. Through discussion and finding of this research, SMEs business owner can optimize their capital spending more effective yet efficient by defining which priority they had to make for expanding business.